2020
DOI: 10.1016/j.ijheatmasstransfer.2020.119587
|View full text |Cite
|
Sign up to set email alerts
|

Thermocapillary flow transition in an evaporating liquid layer in a heated cylindrical cell

Abstract: Motived by recent ground-based and microgravity experiments investigating the interfacial dynamics of a volatile liquid (FC-72, P r = 12.34) contained in a heated cylindrical cell, we numerically study the thermocapillarydriven flow in such an evaporating liquid layer. Particular attention is given to the prediction of the transition of the axisymmetric flow to fully threedimensional patterns when the applied temperature increases. The numerical simulations rely on an improved one-sided model of evaporation by… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Based on the constant Boit numbers of numerical simulations. Liu et al [20] found evaporation plays an opposing role in flow stability. Xu et al [21] further developed the numerical model to account for the convection of gas and proves that evaporation improves the stability of thermocapillary-buoyancy convection.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the constant Boit numbers of numerical simulations. Liu et al [20] found evaporation plays an opposing role in flow stability. Xu et al [21] further developed the numerical model to account for the convection of gas and proves that evaporation improves the stability of thermocapillary-buoyancy convection.…”
Section: Introductionmentioning
confidence: 99%
“…Zahurul Islam and Ying Yin Tsui developed a quasi-3D model to simulate the flow in planar microfluidic devices [ 5 ]. Wenjun Liu et al [ 6 ] and Mohammadbar et al [ 7 ] used the numerical modeling of the evaporation from a liquid layer by considering the phenomena of heat and mass transfer. The kinetic aspects of the Marangoni phenomenon in viscous polymer solutions were investigated by Ye Tian et al [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thermocapillary flow is a type of Maragoni flow induced by the surface tension gradient, which is temperature dependent (Ellahi et al, 2016;Lappa, 2017). The liquid circulation in an evaporating liquid film is inherently interrupted attributed to the presence of a thermocapillary effect (Jiang and Zhou, 2019;Liu et al, 2020). The sign of the surface tension gradient is important in determining the fluid flow direction in an evaporating thin liquid film (Dong et al, 2020).…”
Section: Introductionmentioning
confidence: 99%